RESPONS MUHAMMADIYAH TERHADAP SALAFISME: STUDI ATAS PERGESERAN OTORITAS GERAKAN PURITANISME - Nazaruddin Latif; Nurul Huda; Saifudin Saifudin (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2020)
This study examines Muhammadiyah's response to Salafism in the context of the shift in authority of the puritanism movement. Muhammadiyah as an organization that carries out Islamic movements by focusing on the tajdid movement, one of which is in the field of religion by purifying Islamic teachings from the influence of superstitious practices, bid'ah, and superstition. In its development, the purification movement was also carried out by other groups, one of which was the Salafi. Automatically the presence of the Salafi movement influenced the position of Muhammadiyah, resulting in a shift in the authority of the puritanism movement. Including the stigma of Muhammadiyah as a Salafi. Based on the literature search, Muhammadiyah is still trying to maintain the purification movement. But still trying to show the difference by emphasizing the renewal movement in understanding religion.